O-56 Incidence of malignant mesothelioma in Lombardy, Italy: accuracy of predictive models 2013–2020. (14th March 2023) - Consonni, Dario; Groppi, Alessandro; Pesatori, Angela C; Dallari, Barbara; Mensi, Carolina; Bonzini, Matteo; Rugarli, Sabrina; Stella, Simona
Abstract : Introduction: The Lombardy Mesothelioma Registry (RML) was established in Lombardy Region in 2000 as a regional operative center of the National Mesothelioma Registry (ReNaM-INAIL). It covers a population of 10 million inhabitants and records about a quarter of cases in Italy (60 million inhabitants). In 2016, the RML published incidence predictions over the period 2013-2029, based on age-cohort Poisson regression models applied to 2000-2012 data. Aim of this study is to verify the accuracy of the prediction models and to describe the characteristics of the affected subjects in the period 2013-2020. Material and Methods: The RML collects clinical information on MM cases (all sites) occurring among regional residents at the time of first diagnosis. Information sources include hospital admissions and pathology reports, local health units archives, reports of occupational diseases, and mortality data. In confirmed cases, previous exposure to asbestos is assessed through a standardized questionnaire administered by trained personnel. We extracted from RML databases the record of MM cases collected in the period 2013-2020. Results: Over the period 2013-2020 we had predicted 2102 cases in men (on average 263/year) and 1176 in women (147/year). We recorded 2390 cases in men (299/year) and 1140 (143/year) in women. During the same period, occupational exposure to asbestos was reported by about two-thirds of men and one third of women. Non-occupational exposure to asbestos was reported in <5% in men and about 10% in women. Conclusions: In the period 2013-2020 there was good agreement between predicted and observed MM cases in women, while we recorded 288 more cases than predicted (36/year) in men. The impact of asbestos in Lombardy is still high 30 years after the national ban in 1992, with a total of 7986 cases (5250 in men, 4027 in women) in the period 2000-2020.